Some Aspects of the Relationship Between the Quality of Sheep Milk and Dairy Products - Csanádi, József; Baráné Herczegh, Ottilia; Fenyvessy, József (Acta Agraria Debreceniensis, 2003)
The correlation between the quality of raw milk and the quality of milk products is evident. In spite of this fact we can find only a few references contained exact data related sheep milk. In recent paper we investigated the effect of SCC of sheep milk on the cheese yield (semi hard traditional cheese) and certain texture parameters of yoghurt from sheep milk. We wanted to know the relevant limit values of these properties for dairy applications.In our opinion – in the case of the cheese yield – that the strong negative effect can be experienced when SCC is above 700.000-1 million/cm3.In the case of yoghurt from sheep milk the limit values of SCC can be 1 million/cm3 for Adhesivity and Whey draining and 500.000/cm3 for Hardness. Considering these limit values in the selection of milk become materialise the highest quality of products and the economical production.